Seaweed Diversity and Bioactive Compounds in Panjang Islands, Central Java, Indonesia - Setyati, Wilis Ari; Pramesti, Rini; Putri, Angela Salsalina; Risandhi, Danendra Aquila Azfa; Firdaus, Syifa Shafira; Lumban Gaol, Josua Gabriel (Bogor Agricultural University, Indonesia, 2026)
The biodiversity of seaweed encompasses a wide array of potential bioactive compounds applicable to various industries, particularly pharmaceuticals. This study aimed to collect seaweed diversity data from Panjang Island, Jepara, Central Java, Indonesia, and to identify the bioactive compounds and biological activity of each seaweed species for preliminary screening. Random sampling was used to collect the sample. Qualitative identification of bioactive compounds was performed using the maceration method for extraction, phytochemical screening tests, and pigment identification based on Rf values on TLC. Antibacterial screening tests were performed against Gram-positive (S. aureus) and Gram-negative (E. coli) bacteria, followed by testing against pathogenic fungi (C. albicans) using the disk diffusion method, and an antioxidant test using the DPPH method. The results showed that six species from three phyla (Chlorophyta, Phaeophyta, and Rhodophyta) exhibited distinct morphological characteristics, and the types of bioactive compounds produced by each species differed. The biological activity test results showed a low inhibitory activity. Antibacterial and antifungal biological activities were at the value of (<5 mm), and antioxidant biological activity was (>750 ppm). However, the active compounds and pigments with potential antibacterial, antifungal, and antioxidant properties can be optimized in various fields of bioindustry in the future.